Comparison of cumulative viraemia following treatment initiation with different antiretroviral regimens: a real‐life study in Brazil. Issue 11 (19th November 2019) - Pascom, Ana R; Pinho, Rosana EGG; Rick, Fernanda; Veras, Nazle MC; Perini, Filipe de Barros; Meireles, Mariana V; Pereira, Gerson F; Benzaken, Adele S; Avelino‐Silva, Vivian I
Abstract: Introduction: The relative efficacy of different antiretroviral (ART) regimens has been extensively evaluated in the context of clinical trials, using HIV viral load (VL) measurements at pre‐specified timepoints after ART onset. However, data from real‐life studies using combined longitudinal measurements of cumulative viraemia are scarce. This study aimed to address the independent effect of different ART regimens on HIV cumulative viraemia over the first 12 months after treatment initiation, using programmatic data from the Ministry of Health of Brazil. Methods: Retrospective cohort study analysing cumulative viraemia under the most frequently used ART regimens in Brazil (tenofovir, lamivudine and dolutegravir (regimen 1); tenofovir, lamivudine and efavirenz (regimen 2); tenofovir, lamivudine and ritonavir‐boosted atazanavir (regimen 3)). Results and Discussion: We included 112, 243 patients >12 years old who received their first ART prescription between January 2014 and August 2017. Univariate analysis indicated that cumulative viraemia was significantly lower in patients receiving regimen 1 as compared with those receiving regimens 2 or 3 ( p <0.0001 for both pairwise comparisons). In a multivariable analysis adjusted for age, sex, baseline T CD4+ counts and baseline HIV VL, ART regimen persisted with statistically significant effect on 12‐month cumulative viraemia. The model predicted a 45‐unit increase in log10 copy‐days/mL cumulative viraemia for regimen 2 as compared with regimen 1, and a 70‐unit increase in log10 copy‐days/mL cumulative viraemia for regimen 3 as compared with regimen 1 (95%CI 41 to 49 and 61 to 79 respectively; p <0.001 for both comparisons). In models restricted to youths (13 to 24 years old) and female patients, ART regimen had similar effects. ART regimen with dolutegravir in association with a tenofovir‐lamivudine backbone was superior to regimens containing efavirenz or boosted atazanavir in reducing HIV VL, as shown by cumulative viraemia over the first 12 months after treatment initiation. The superiority persisted even after adjusting the analysis for potential confounders. Conclusions: Our findings could bring direct benefits to patients as suggested by lower viral replication during treatment, lower risk of HIV transmission, and a potential reduction in resistance mutations in the initial 12 months under ART.